حرية التعبير في الدستور الج ا زئري بيف التكريس والتقييد - خالدي, عادل; بن الصــــغير الجيلاني, الجيلاني (University of Eloued جامعة الوادي, 2020)
إن حق الإنسان في حرية التعبير ضرورة لابد منيا، لأن الإنسان الذي لا يستطيع أن يفتح فاه لا يمكن لو أن يطالب ببقية الحقوق. وعمى ىذا الأساس فإن موضوع حرية التعبير من الموضوعات التي شغمت اىتمام الباحثين في ىذا الزمن، و سبب ذلك يعود إلى تعدد منافذ الاتصال و تنوع وسائمو و كثرتيا، و خاصة مع التطور السريع في مجال الاتصالات. واذا كانت الش ا رئع عمى اختلبفيا قد تباينت في كمية و نوعية الضوابط التي ترسم حدود ىذه الحرية فإنيا تتفق في المجمل عمى أنو لا مكان في حياة أي إنسان لشيء اسمو حرية التعبير المطمقة، و عميو فإن التشريع الج ا زئري قد أعطى أىمية كبرى لتكريس ىذه الحرية و ضبطىا كي يحفظ ليا صفاءىا و نقاءىا. ومن بين تمك الضوابط تجنب الإض ا رر بالنظام العام و الآداب العامة، و من ثم لا يجوز لممعبر عن أ ريو أن يسبب ضر ا ر للؤمن الوطني أو الاقتصاد الوطني أو يخدش الآداب العامة، كما يجب عميو تجنب الترويج للئج ا رم، إضافة إلى ذلك عميه احت ا رم المعتقدات و المقدسات الدينية. وخلبصة القول أن التشريع الج ا زئري يؤكد عمى أن ممارسة حرية التعبير و إن كانت حقا مشروعا فإنيا تقتضي أن تكون أداة لمبناء و ليست معولا لميدم..The human right to freedom of speesh is an inevitable necessity, because a person who cannot speak cannot claim the rest of the rights . On this basis, freedom of expression's issue is one of the topics that have occupied the interest of researchers nowadays due to the multiplicity of communication outlets and the diversity of its means and their abundance, especially with the rapid development in the field of communication. Moreover if the different laws differed in the quantity and quality of the controls that delineate the limits of this freedom, then they generally agree that there is no place in any person's life for something called absolute freedom of expression. accordingly, the Algerian legislation has given great importance to the consecration and control of this freedom To preserve its clarity and purity. Among these controls, avoiding harm to the public order and morals, therefore it is not permissible for whom expressing his/her opinion to cause harm to national security, economy or to disturb public morals, also he/she must avoid promoting criminality and respect religious beliefs and sanctities . to sum up, the Algerian legislation affirms that freedom of expression's exercise, even if it is a legitimate right, requires that it must be a tool for construction not a support for demolition.
مذكرة